Cop26 and beyond: participation and gender – more of the same? - Karen Morrow (Transnational Legal Theory, 2022)
This article considers gender equality in the context of the most recent United Nations Framework Convention on Climate Change (UNFCCC) Conference of Parties (CoP), CoP26. Gender equality issues are now widely recognised within global climate change governance, playing an ongoing role within it. The CoP does not function in isolation and its regime setting is significant, in particular, in the work of UNFCCC constituted bodies and the Intergovernmental Panel on Climate Change (IPCC). Other parts of the United Nations, such as the Commission on the Status of Women (CSW66) can also offer important contributions to gender; and civil society too plays a vital role in this aspect of climate governance. These elements and the interplay between them have shaped gender issues at CoP26, as has the global pandemic. While gender equality is a live issue in global climate governance, leveraging substantial, substantive, action by states to address it remains problematic.